Impact of ultrasonic dispersion on the photocatalytic activity of titania aggregates - Hoai Nga Le,; Babick, Frank; Kuehn, Klaus; Minh Tan Nguyen,; Stintz, Michael; Cuniberti, Gianaurelio (Giovanni) (Beilstein Journal of Nanotechnology, 2015)
The effectiveness of photocatalytic materials increases with the specific surface area, thus nanoscale photocatalyst particles are preferred. However, such nanomaterials are frequently found in an aggregated state, which may reduce the photocatalytic activity due to internal obscuration and the extended diffusion path of the molecules to be treated. This paper investigates the effect of aggregate size on the photocatalytic activity of pyrogenic titania (Aeroxide® P25, Evonik), which is widely used in fundamental photocatalysis research. Well-defined and reproducible aggregate sizes were achieved by ultrasonic dispersion. The photocatalytic activity was examined by the color removal of methylene blue (MB) with a laboratory-scale setup based on a plug flow reactor (PFR) and planar UV illumination. The process parameters such as flow regime, optical path length and UV intensity are welldefined and can be varied. Our results firstly show that a complete dispersion of the P25 aggregates is not practical. Secondly, the photocatalytic activity is not further increased beyond a certain degree of dispersion, which probably corresponds to a critical size for which UV irradiation can penetrate the aggregate without significant obscuration.
CRIS-Team Scopus Importer:2023-03-20
Keywords: AOPs; Reaction rate constant; Turbidity; Ultrasonic energy; Wastewater treatment